The viability of transforming stormwater detention ponds into infiltration ponds on the Cape Flats, South Africa - Tanyanyiwa, Craig Tinashe (Department of Civil Engineering, 2024)
The City of Cape Town (CoCT) is committed to implementing various measures to increase water security, including groundwater use with managed aquifer recharge (MAR). A previous simulation-based study found that stormwater harvesting (SWH) via MAR was viable in Cape Town and proposed implementing MAR in retrofitted detention ponds overlying the unconfined Cape Flats Aquifer (CFA). This study investigated the viability of retrofitting detention ponds in Cape Town to facilitate urban MAR at the neighbourhood scale. The research methods used included desktop analysis, field investigations, unstructured participant observations, laboratory investigations, computational hydrological modelling, and financial analysis. A field-scale case study in Mitchells Plain, Cape Town, demonstrated the importance of community engagement in successfully implementing detention pond retrofit projects. The developmental nature of retrofit projects requires collaboration between city officials and communities with continuous outreach efforts to address conflicting priorities and interests. This approach diverges from conventional engineering practices and requires a significant time investment. A computational hydraulic simulation using the PCSWMM Professional (version 7.5) software revealed that retrofitting a detention pond to improve infiltration led to a MAR increase of 290%. Laboratory studies showed that stormwater from the CoCT, which was of poor quality, could be treated by allowing it to infiltrate through the media from the CFA. This resulted in significant reductions in pollutants at varying depths in the vadose zone, with up to 99% reduction in contaminant concentrations. The resulting effluent met the established guidelines for six of the eight contaminants examined in this study. A financial viability assessment was conducted for two scenarios. In the shallow water table scenario, the benefit-cost ratio (BCR) was 0.55, indicating that the project was not financially feasible. However, in the alternate 'CFA groundwater use' scenario, the BCR was 1.14, demonstrating its financial viability. Furthermore, the unit reference value of the scenario was lower than that of desalination, suggesting that combining groundwater use with SWH via MAR is economically more attractive than seawater desalination. Overall, this study provides evidence for the viability of retrofitting detention ponds for urban MAR in Cape Town from technical, social, and economic perspectives, considering the challenges and potential of the South African context. These outcomes were then used to develop a practical 'middle-out' approach for retrofitting detention ponds for urban MAR in Cape Town.